2007
DOI: 10.1097/wnr.0b013e3282202c61
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cingulate reflects susceptibility to framing during attractiveness evaluation

Abstract: Human cognitive decisions can be strongly susceptible to the manner in which options are presented ('framing effect'). Here we investigated the neural basis of response adjustments induced by changing frames during intuitive decisions. Evidence exists that the anterior cingulate cortex plays a general role in behavioral adjustments. We hypothesized, therefore, that the anterior cingulate cortex is also involved in the 'framing effect'. Our hypothesis was tested by using a binary attractiveness judgment task ('… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 15 publications
(19 reference statements)
1
43
0
5
Order By: Relevance
“…Furthermore, the results suggested that brands might function as subconscious presentiments that influenced the decision-making process even before the participants began thinking about advantages and disadvantages of the cars. This suggestion is supported, to some degreed, by Deppe et al (2007) and their investigations of the neural processing of magazine brands.…”
Section: Brand Researchmentioning
confidence: 68%
See 1 more Smart Citation
“…Furthermore, the results suggested that brands might function as subconscious presentiments that influenced the decision-making process even before the participants began thinking about advantages and disadvantages of the cars. This suggestion is supported, to some degreed, by Deppe et al (2007) and their investigations of the neural processing of magazine brands.…”
Section: Brand Researchmentioning
confidence: 68%
“…Therefore, a central aspect of this important marketing-mix instrument is the choice of product-and brandadequate marketing channels, in order to define the optimal frame for the presentation of a brand (Pasternack, 1985;Eliashberg and Steinberg, 1987;Choi, 1991;Lee and Staelin, 1997). In two similarly constructed studies, Deppe et al (2005aDeppe et al ( , 2007 examined the neural correlates of this ''framing effect.'' A main finding of their investigations was that the medial prefrontal cortex and the anterior cingulate cortex, in particular, play a central role for the integration of implicit framing information, for example, the importance of emotions and unconscious memories in the decision-making process.…”
Section: Distribution Policymentioning
confidence: 99%
“…Indeed, binary choices involving the subject's first-choice brand were associated with an increased activity in the cingulate cortex whereas the absence of prior preference led to a stronger use of the parietal and occipital cortices associated with working memory, reasoning and visual processing (Deppe, Schwindt, Kugel, et al, 2005). Likewise, the activation of the cingulate cortex was associated with the processing of implicit brand information such as the image or reputation of news magazine brands; this could be influencing the evaluation of the credibility of the news headlines (Deppe, Schwindt, Krämer, et al, 2005) and the perception of the advertisements contained in these news magazines (Deppe et al, 2007). However, on a related question about whether brands could even be processed in a similar way to persons, fMRI measures during semantic judgements showed that the processing of ''brand personalities'' activated object-processing regions, as a contrary to the processing of persons (Yoon, Gut-chess, Feinberg, & Polk, 2006).…”
Section: Solnais C Andreu-perez J Sánchez-fernández J and Andrmentioning
confidence: 99%
“…In the forced-choice-task, subjects had to evaluate each of the selected packages four times (120 decisions) according to their attractiveness. In order to achieve a higher comparability with other studies within this special field of research (e.g., Deppe et al, 2005aDeppe et al, , 2007, we renounced rest periods during our evaluation task. Participants were advised to avoid head movements during the measurement.…”
mentioning
confidence: 99%
“…This brain structure seems to be involved in the generation of emotions, the emotional evaluation of incoming stimuli, the prediction of expected rewards and decision-making ; The anterior cingulate cortex is in general associated with emotions, response selection, initiation, motivation, reward-based learning, and goal-directed behavior (Devinsky et al, 1995;Bush et al, 2002;Dalgleish, 2004). Due to its close connection to other brain structures, such as the orbitofrontal cortex, this brain area might be concerned with integrating implicit information and emotions in the decision-making process (Bush et al, 2002;Deppe et al, 2005aDeppe et al, , 2007. Beyond this, the anterior cingulate cortex seems to be involved in the regulation of cognitive and emotional processing, through the salience evaluation of emotional and motivational information, it might help to adjust corresponding emotional responses (Bush et al, 2002).…”
mentioning
confidence: 99%